Theoretical energy analysis of Cascade refrigeration system using low Global warming potential refrigerants. (2022) - Soni, Shubham; Mishra, Punit; Maheshwari, Govind; Verma, Devendra S.
Abstract: In the refrigeration sector, refrigerants with low global warming potential (GWP) have become the need of the hour. The presented work aims to investigate the use of low GWP refrigerant pairs like NH3 /CO2, R1234yf/CO2, and R1234ze/CO2 in the Cascade refrigeration system. This study will help in checking the utility of chosen refrigerants. For the analysis, a mathematical model of a cascade system is prepared and performance parameters like Energy efficiency ratio, compressor power, coefficient of performance are compared for chosen refrigerant pairs. During this study, the Condenser and the evaporator temperature are changed 318 K to 333 K and 228 K to 243 K respectively. It is observed that the highest coefficient of performance is obtained for NH3 /CO2 which is 8.097% and 4.135 % higher than that obtained for R1234yf/CO2 and R1234ze/CO2 respectively. The compressor power is least consumed for NH3 /CO2 which is 7.498 % and 3.982 % less than R1234yf/CO2 and R1234ze/CO2 respectively. Thus NH3 /CO2 is the best choice among all the selected pairs for this study.